Effect of Different Solvent Ratios (Water/Ethylene Glycol) on the Growth Process of CaMoO4 Crystals and Their Optical Properties - Marques, V. S.; Cavalcante, L. S. [UNESP]; Sczancoski, J. C.; Alcantara, A. F. P.; Orlandi, Marcelo Ornaghi [UNESP]; Moraes, E.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Siu Li, M.; Santos, M. R. M. C. (Amer Chemical Soc, 2010)
In this paper, calcium molybdate (CaMoO4) crystals (meso- and nanoscale) were synthesized by the coprecipitation method using different solvent volume ratios (water/ethylene glycol). Subsequently, the obtained suspensions were processed in microwave-assisted hydrothermal/solvothermal systems at 140 degrees C for 1 h. These meso- and nanocrystals processed were characterized by X-ray diffraction (X R I)), Fourier transform Raman (FT-Raman), Fourier transform infrared (FT-IR). ultraviolet visible (UV-vis) absorption spectroscopies, held-emission gun scanning electron microscopy (FEG-SEM). transmission electron microscopy (TEM). and photoluminescence (PL) measurements. X RI) patterns and FT-Raman spectra showed that these meso- and nanocrystals have a scheelite-type tetragonal structure without the presence of deleterious phases. FT-IR spectra exhibited a large absorption band situated at around 827 cm(-1), which is associated with the Mo-O anti-symmetric stretching vibrations into the [MoO4] clusters. FEG-SEM micrographs indicated that the ethylene glycol concentration in the aqueous solution plays an important role in the morphological evolution of CaMoO4 crystals. High-resolution TEM micrographs demonstrated that the mesocrystals consist of several aggregated nanoparticles with electron diffraction patterns of monocrystal. In addition, the differences observed in the selected area electron diffraction patterns of CaMoO4 crystals proved the coexistence of both nano- and mesostructures, First-principles quantum mechanical calculations based on the density functional theory at the B3LYP level were employed in order to understand the band structure find density of states For the CaMoO4. UV-vis absorption measurements evidenced a variation in optical band gap values (from 3.42 to 3.72 cV) for the distinct morphologies. The blue and green PI. emissions observed in these crystals were ascribed to the intermediary energy levels arising from the distortions on the [MoO4] clusters clue to intrinsic defects in the lattice of anisotropic/isotropic crystals.